Cruise CAGE15-4 - Bünz, Stefan (CAGE – Centre for Arctic Gas Hydrate, Environment and Climate Report Series, 2023)
CAGE 15-4 was a short 3-day cruise with only one major objective which is to repeat a P-cable survey covering the active seeps on the Vestnesa Ridge in order to develop time-lapse 4D seismic studies of gas leakage. Three OBS stations were also deployed during the 3D seismic survey. The cruise may be known as: CAGE15_4